CaO‐containing LaCO3OH nanogears and their luminescence and de‐NOx properties. Issue 12 (20th June 2018) - Zahir, Md. Hasan; Iwamoto, Yuji; Rahman, Mohammad Mizanur; Aziz, Md. Abdul; Chowdhury, Shakhawat; Ahmad, S. H. A.; Qamaruddin, Muhammad
Abstract: Large‐scale, uniform, monodisperse LaCO3 OH cherry‐blossom‐like nanogears and/or nanocubes have been synthesized under hydrothermal reaction conditions. Upon the addition of only 5 mol% Ca 2+ ions into a La nitrate salts solution with pH 8.5, LaCO3 OH crystals with novel cubic or nanogear structures are formed in the hexagonal phase. The hydrothermal reactions were carried out without the addition of a template or catalysts. Both 24 hour and 48 hour hydrothermal reactions yield 100% pure LaCO3 OH with no irregular particles. We examined the photoluminescence properties of the as‐synthesized powders of the pure LaCO3 OH nanogears and found one broad emission band centered at 394 nm after excitation at λ = 280 nm. The NO reduction activity was also examined over highly dispersed CaO‐containing La2 O3 obtained after calcination the LaCO3 OH at 800 ○ C for 2 hours. The CaO‐containing La2 O3 catalysts showed good stability for NO reduction with CH4 in the presence of O2 and H2 O vapor. Abstract : De‐NOx properties over CaO‐containing La2 O3 catalysts.